A multicenter phase II study of TAS-102 monotherapy in patients with pre-treated advanced gastric cancer (EPOC1201). (July 2016) - Bando, Hideaki; Doi, Toshihiko; Muro, Kei; Yasui, Hirofumi; Nishina, Tomohiro; Yamaguchi, Kensei; Takahashi, Shunji; Nomura, Shogo; Kuno, Hirofumi; Shitara, Kohei; Sato, Akihiro; Ohtsu, Atsushi
Abstract: Aim: American phase I studies have reported that the recommended dose of TAS-102 (trifluridine/tipiracil) was 25 mg/m 2 twice a day (b.i.d.), although this schedule did not provide clinically relevant improvements in a phase II study of advanced gastric cancer (AGC). However, a pivotal phase III study revealed that TAS-102 at 35 mg/m 2 b.i.d. provided a clinically relevant improvement in overall survival (OS) among patients with metastatic colorectal cancer. Therefore, we re-evaluated the efficacy, safety, and pharmacokinetic parameters of TAS-102 at 35 mg/m 2 b.i.d among Japanese patients with AGC. Methods: All patients had undergone one or two previous chemotherapy regimens that contained fluoropyrimidine, platinum agents, and taxanes or irinotecan. The primary end-point target was a disease control rate (DCR) of ≥50% after 8 weeks of the 35 mg/m 2 b.i.d. schedule. Results: Twenty-nine patients were assessable after completing the 35 mg/m 2 b.i.d. schedule. The investigator-determined DCR was 65.5% (95% confidence interval [CI], 45.7–82.1%) and the independent central review's DCR was 51.9% (95% CI, 31.9–71.3%); both results exceeded the primary end-point target. The median progression-free survival and OS were 2.9 months (95% CI, 1.1–5.3 months) and 8.7 months (95% CI, 5.7–14.9 months), respectively. The grade III/IV adverse events included neutropenia (69.0%), leucopaenia (41.4%), anaemia (20.7%), and anorexia (10.3%). No AGC-specific toxicities were detected. Conclusions: The 35 mg/m 2 b.i.d. dose of TAS-102 provided positive efficacy and an acceptable toxicity profile in patients with AGC. A randomised, double-blind, placebo-controlled, phase III study is ongoing to validate these findings. Clinical trial registration number: UMIN000007421 Highlights: We evaluated TAS-102 among Japanese patients with advanced gastric cancer (AGC). TAS-102 (35 mg/m 2 twice a day) provided a disease control rate of 65.5% for AGC. The progression-free and overall survivals were 2.9 and 8.7 months. There were no gastric cancer-specific toxicities or complications. A randomised double-blind phase III study is ongoing to validate our findings.